Room‐Temperature Diffusion‐Induced Extraction for Perovskite Nanocrystals with High Luminescence and Stability. Issue 6 (21st April 2021) - Yao, Fang; Liu, Yongjie; Xu, Yalun; Peng, Jiali; Gui, Pengbin; Liang, Jiwei; Lin, Qianqian; Tao, Chen; Fang, Guojia
Abstract: Metal halide perovskite nanocrystals (NCs) serve as a kind of ideal semiconductor for luminescence and display applications. However, the optoelectronic performance and stability of perovskite NCs are mainly subjected to current ligand strategies since these ligands exhibit a highly dynamic binding state, which complicates NC purification and storage. Herein, a method named diffusion‐induced extraction is developed for crystallization (DEC) at room temperature, in which silicone oil serves as a medium to separate the solvent from perovskite precursors and diethyl ether promotes the nucleation, leading to highly emissive perovskite NCs. The formation mechanism of NCs using this approach is elucidated, and their optoelectronic properties are fully characterized. The resultant NCs ink exhibits a high photoluminescence quantum yield (PLQY) over 90% with a narrow full width at half maximum of 17 nm. The DEC method strengthens the interaction between ligand and NCs via the hydrophobic silicone oil. Therefore, the NCs maintain almost 95% of their initial PLQYs after aging more than seven months in air. The findings will be of great significance for the continued advancement of high PLQY perovskite NCs through a better understanding of formation dynamics. The DEC strategy presents a major step forward for advancing the field of perovskite semiconductor nanomaterials. Abstract : Perovskite nanocrystals (NCs) wrapped with silicone oil and octylamine ligands show high photoluminescence quantum yields, stable emission peaks, and long‐term storage stability. Silicone oil separates solvent from perovskite precursor solution and protects the NCs from moisture and oxygen.